MEDICAL STUDENTS’ EXPERIENCES WITH DYING PATIENTS: IDENTIFYING EDUCATIONAL NEEDS IN THE EASTERN CONTEXT - Dharmatika, I Made Pramana; Suhoyo, Yoyo; Prihatiningsih, Titi Savitri (Universitas Gadjah Mada, 2023)
Background: The death of a patient is an event that could trigger medical students’ emotional reactions during clinical rotation. This study aimed to identify medical students’ preparedness in dealing with patients’ death and their educational needs through their lived experience.Methods: This was a qualitative study with a descriptive phenomenological approach. Purposive sampling was used to select medical students with experience caring for dying patients during clinical rotation. Data were collected through semi-structured interviews. Colaizzi’s method was used to analyze data.Results: The experience of six medical students showed medical students’ difficulties in discussing end-of-life with family members, giving emotional support to dying patients, and supporting grieving family members. Hierarchies and hidden curriculums influenced the interaction between medical students and medical staff during end-of-life care provision. The educational needs of medical students were teaching and learning about communication skills and attitudes in caring for dying patients, awareness of local culture in end-of-life care, the opportunity to observe medical staff communicate with dying patients and family members, and debriefing with healthcare team members after patients’ death.Conclusion: The findings of this study have provided insight into medical students’ experiences in dealing with patients’ death and their problems. Medical schools should prepare medical students to care for dying patients through curriculum development.